Improvement of metabolic heat accumulation for hyperthermophilic composting system: influencing factors and microbial communities - Zhiquan Wang; Zhe Chen; Shunfeng Jiang; Huachang Jin; Ruihuan Chen; Suqing Wu; Chunzhen Fan; Min Zhao; Xiaomei Gong; Minghai Xu; Xiangyong Zheng (Environmental Sciences Europe)
Abstract Hyperthermophilic composting (HTC) system has attracted significant attention because of the extreme high temperature and special hyperthermophiles, but few researches were clearly explained how to achieve the hyperthermophilic conditions. Thereby, this study further analyzed the main factors affecting the metabolic heat accumulation based on the acclimated hyperthermophilic Bacillus thermoamylovorans. In total, our observations showed that the higher start-up temperature and easily degradable organic matter (OM) could promote the metabolic heat accumulation, the low OM and high heavy metal content had a negative effect on the rise of temperature. Especially, excessive easily degradable OM did not further increase the maximum temperature, but prolonged the thermophilic stage instead. Besides, the richness and diversity of bacteria were significantly decreased when the thermophilic stage stepped into hyperthermophilic stage, with the Sphingobacterium, Bacillus, and Lysinibacillus became the dominant bacterial communities. Among them, the acclimated Bacillus thermoamylovorans could account for 31% during the thermophilic stage, but rapidly decreased to 4% in hyperthermophilic stage. No strong dependence between rising temperature and diversity/richness of hyperthermophilic microbial communities was observed, which indicated that the existence of hyperthermophiles was one of necessary, but not sufficient conditions to achieve the hyperthermophilic conditions.